The Alucitidae (Lepidoptera) of Malawi with descriptions of five new species - Ustjuzhanin, Petr; Kovtunovich, Vasily (Zootaxa, 2016)
An overview of Alucitidae species from Malawi is presented, with 20 species reported. Five of them are described as new for science: Alucita nyasa Ustjuzhanin & Kovtunovich sp. nov., Alucita aarviki Ustjuzhanin & Kovtunovich sp. nov., Alucita malawica Ustjuzhanin & Kovtunovich sp. nov., Alucita murphy Ustjuzhanin & Kovtunovich sp. nov. and Alucita sochivkoi Ustjuzhanin & Kovtunovich sp. nov. Four new synonyms are established. The following species are considered synonyms of Alucita seychellensis (T.B.Fletcher, 1910): Alucita granata (Meyrick, 1921) syn. nov., and Alucita imbrifera (Meyrick, 1929) syn. nov. Alucita myriodesma (Meyrick, 1929) is considered a junior synonym of Alucita ectomesa (Hering, 1917) syn. nov., and Alucita isodina (Meyrick, 1920) a synonym of Alucita spicifera (Meyrick, 1911) syn. nov. All the Alucitidae species are reported for the Malawian fauna for the first time.